Study of Van der Waals surfaces along the layer of TlInS2 and TlInS2 <0.1%V> crystals irradiated with γ-quanta - Salmanov, F.T.; Sardarly, R.M.; Mukhtarov, R.M.; Aliyeva, N.A.; Mammadov, R.A. (Physics and Chemistry of Solid State, 2026)
The aim of this study is to determine the fundamental physical regularities of nanoplastic deformation on the surfaces of gamma-irradiated layered TlInS2 and 0.1% vanadium-doped TlInS2 crystals and to study their general kinetic processes that influence surface structuring at the nanoscale. This research focuses on the regularities in the formation property of corrugated and dislocated structures in surface layers and the impact of the kinetics of surface structures in a different media. Geometric dimensions and profiles of structural formations in Van der Waals surface layers of TlInS2 and TlInS2 <0.1%V> layered crystals irradiated with γ-quanta were determined by atomic force microscopy. Due to the formation nature of whisker and corrugation elements, deformation in the surface layers is observed in both initial and final stages, which goes along with the natural oxidation process. An analysis was conducted on the factors responsible for the characteristics of plastic flow.